AS DIFICULDADES SUPERADAS POR PEQUENOS EMPREENDEDORES NOS SETORES DE PRODUTOS E SERVIÇOS NA REGIÃO OESTE E NORTE DA CAPITAL DE SÃO PAULO - Novaes, Marcos Antonio (2014)
According to the SEBRAE (2010) research in Brazil, microenterprise represent 5,6 to 6 million of company. Meet an important role for the National GDP (PIB). The mortality of these business surveys show that about 75% fail to remain on the market beyond the initial six months. Opening these small businesses is due in many cases, the need arising from unemployment. The previously registered entrepreneur can use your compensation and the Guarantee Fund for Time of Service to start a new enterprise. Most often, these businesses do not have adequate support or constitute a business plan, differently of other countries like the United States and Canada, where is a basic condition for the beginning of a project. Moreover, contrary to the research of mortality (SEBRAE, 2010), there are small businesses that survive over time, from the sidelines of all the oscillation of the market, both internal and external. This paper will examine six micro enterprises of the northern and western regions of São Paulo, capital, and with small businesses that are more than five years in the market and formed near the subway terminals, Santana and Butantã. Also, show what difficulties transposed by these entrepreneurs to give longevity to your business.